Implementation of Artificial Intelligence in the Legal Protection of Cyber Bullying Victims on Social Media According to Law No. 1 of 2023 - Cepi Noval (Journal of Social Science, 2024)
Cyberbullying on social media is a serious problem that can negatively impact the mental health and well-being of victims. Lack of supervision in the family, school, community, and individual environments causes cyberbullying. Article 433 paragraph (1), and paragraph (2) of Law No. 1 of 2023 concerning the Criminal Code (KUHP) provides a new legal basis regarding defamation through social media and will be enforced in 2026. Artificial intelligence (AI) can be an innovative solution in addressing this problem. The purpose of the study is to analyze the legal protection of victims of cyber bullying on social media according to Law No. 1 of 2023 and explore the potential integration of AI in its handling. The research method used is normative juridical, using a legislative approach and an analytical approach. The results of the study show that although Law No. 1 of 2023 provides a clear legal framework, its implementation is still hampered by a lack of resources and understanding in the community. On the other hand, AI integration has proven to be effective in detecting and analyzing bullying behavior on social media, providing support to victims, and speeding up the investigation process by authorities. This study concludes that legal protection for victims of cyber bullying can be improved through the integration of artificial intelligence. Therefore, collaboration between the government, social media platform providers, and technology experts is needed to create more effective and responsive solutions to the problem of cyber bullying in society